A bibliometric study of the cultural models in international business research - Reis, Nuno (2018)
Culture and the influence of national cultures and cultural differences have been widely studied in International Business (IB) research especially over the past three decades. To better understand what culture actually means and its implications on firms’ international operations, several cultural models and taxonomies have been put forward. In this paper we review the main cultural models in the extant IB research – Hofstede’s (1980), Hall’s (1976) and Troompenaars’ (1993) – and Kogut and Singh’s (1988) concept of cultural distance. In a bibliometric study of over 3,600 articles published in seven top ranked journals for IB research, we examine citations and co-citations to assess the relative use of the cultural models and the ties binding authors and theories studied. This study offers a wealth of information on the current state of IB-related research using culture that may be used to better understand the intellectual structure of the sub-field of cultural issues in IB studies but also to identify gaps for future inquiry. The results help setting a profile of the network of knowledge and permit us to conclude that Hofstede’s (1980) taxonomy on cultural characteristics is the most cited cultural taxonomy and holds ties to many of the core streams of IB-related research. In fact, despite the well-known criticisms, there is an increasing use of Hofstede’s dimensions.